2015
DOI: 10.4062/biomolther.2014.075
|View full text |Cite
|
Sign up to set email alerts
|

Genistein from Vigna angularis Extends Lifespan in Caenorhabditis elegans

Abstract: The seed of Vigna angularis has long been cultivated as a food or a folk medicine in East Asia. Genistein (4′,5,7-trihydroxyisoflavone), a dietary phytoestrogen present in this plant, has been known to possess various biological properties. In this study, we investigated the possible lifespan-extending effects of genistein using Caenorhabditis elegans model system. We found that the lifespan of nematode was significantly prolonged in the presence of genistein under normal culture condition. In addition, genist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…It remains unclear how similar their biological effect is, but Lee et al . () report genistein to significantly increase lifespan and stress tolerance of wild‐type C. elegans lifespan at 50 and 100 μ m concentrations.…”
Section: Resultsmentioning
confidence: 97%
“…It remains unclear how similar their biological effect is, but Lee et al . () report genistein to significantly increase lifespan and stress tolerance of wild‐type C. elegans lifespan at 50 and 100 μ m concentrations.…”
Section: Resultsmentioning
confidence: 97%
“…Compounds published to increase lifespan in either mice (m), flies (f), or worms (w) are indicated. The candidates include Valproic acid, an HDAC inhibitor previously shown to increase lifespan in worms (Evason et al, 2008), Trichostatin A, another HDAC inhibitor previously shown to increase lifespan in both worms (Calvert et al, 2016) and flies (Tao et al, 2004), LY-294002, a PI3 Kinase inhibitor, shown to increase lifespan in both worms (Calvert et al, 2016) and flies (Moskalev and Shaposhnikov, 2010), Estradiol, shown to increase lifespan in worms (Ye et al, 2014), Rapamycin, also known as sirolimus, well known to extend lifespan in worms (Calvert et al, 2016), flies (Bjedov et al, 2010), and mice (Harrison et al, 2009), Genistein, an angiogenesis inhibitor, shown to extend lifepan in worms (Lee et al, 2015), and Wortmannin, another PI3 Kinase inhibitor, shown to extend lifespan in flies (Danilov et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Genistein (4′, 5, 7-trihydroxyisoflavone) is a natural polyphenol found in soy and other legumes, such as Vigna angularis, that reportedly extended the lifespan of Caenorhabditis elegans [ 88 , 89 ]. Skin anti-ageing effects have been accredited to this polyphenol, as it can bind to estrogen receptors, enhance collagen biosynthesis, act as an antioxidant and protect from UV-induced photodamage [ 88 ].…”
Section: Natural Compounds Found To Activate Nrf2 Ups or Alpmentioning
confidence: 99%